Cost-of-illness studies in heart failure: a systematic review 2004-2016 - Lesyuk, Wladimir; Kriza, Christine; Kolominsky-Rabas, Peter (Bmc Cardiovascular Disorders, 2018)
BACKGROUND: Heart failure is a major and growing medical and economic problem worldwide as 1-2% of the healthcare budget are spent for heart failure. The prevalence of heart failure has increased over the past decades and it is expected that there will be further raise due to the higher proportion of elderly in the western societies. In this context cost-of-illness studies can significantly contribute to a better understanding of the drivers and problems which lead to the increasing costs in heart failure. The aim of this study was to perform a systematic review of published cost-of-illness studies related to heart failure to highlight the increasing cost impact of heart failure. METHODS: A systematic review was conducted from 2004 to 2016 to identify cost-of-illness studies related to heart failure, searching PubMed (Medline), Cochrane, Science Direct (Embase), Scopus and CRD York Database. RESULTS: Of the total of 16 studies identified, 11 studies reported prevalence-based estimates, 2 studies focused on incidence-based data and 3 articles presented both types of cost data. A large variation concerning cost components and estimates can be noted. Only three studies estimated indirect costs. Most of the included studies have shown that the costs for hospital admission are the most expensive cost element. Estimates for annual prevalence-based costs for heart failure patients range from 868 for South Korea to 25,532 for Germany. The lifetime costs for heart failure patients have been estimated to 126.819 per patient. CONCLUSIONS: Our review highlights the considerable and growing economic burden of heart failure on the health care systems. The cost-of-illness studies included in this review show large variations in methodology used and the cost results vary consequently. High quality data from cost-of-illness studies with a robust methodology applied can inform policy makers about the major cost drivers of heart failure and can be used as the basis of further economic evaluations.
EVALuna2:35790

Sarcopenia Assessments as Predictors of Overall Survival in Patients with Metastatic Renal Cell Carcinoma - Kuemmerl, Luca; Lesyuk, Wladimir; Goebell, Peter; Kahlmeyer, Andreas (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Sarcopenia assessments as predictors of overall survival in patients with metastatic renal cell carcinoma - Kümmerl, Luca; Kraulich, Matthias; Lesyuk, Wladimir; Binninger, Adrian; Goebell, Peter; Kahlmeyer, Andreas (Urologic Oncology-Seminars and Original Investigations, 2023)
Background: Sarcopenia represents an important prognostic marker in tumor patients. However, measurement methods and threshold values are not uniformly defined. The aim of this study is therefore to determine the prognostic value of current definitions of sarcopenia in patients with metastatic renal cell carcinoma treated with tyrosine-kinase-inhibitors (TKIs). Methods: In 93 patients with metastatic renal cell carcinoma, sarcopenia was assessed based on manually assisted software measurements of sarcopenia indices based on different muscle areas. Whole muscle area and psoas muscle area at L3 were estimated and adjusted to patient's height in routine CT imaging before the start of first-line TKI therapy. The correlation of different sarcopenia definitions to overall survival was investigated in a univariate analysis as well as in a multivariate analysis. Results: The mean patients’ age at inclusion was 65.8 years (21–86 years). Median survival was 12.3 months (IQR: 5.7–29.8 months), and mean survival was 18.8 months (SD: 17.2 months). As the definitions of sarcopenia differ considerably, 7.6% to 96.7% of the patients were classified as sarcopenic. In univariate analysis, sarcopenia was significantly associated with overall survival. Multivariate analysis, taking into account the Memorial Sloan Kettering Cancer Center risk score, revealed that some sarcopenia-indices are additional and independent prognostic markers. The risk of death was approximately doubled in sarcopenic patients. Conclusions: Sarcopenia is an important prognostic factor in patients with metastatic renal cell carcinoma treated with TKIs. Multivariate analysis demonstrates a doubling of the risk of death in sarcopenic patients. The assessment of sarcopenia can be performed by the analysis of routine staging imaging using indices of the total muscle area or the psoas muscle area.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Overall survival; Prognostic factor; Psoas muscle; Renal cell carcinoma; Sarcopenia; Skeletal muscle; Tyrosine kinase inhibitors